Entropy generation minimization: Darcy-Forchheimer nanofluid flow due to curved stretching sheet with partial slip. (February 2020) - Hayat, Tasawar; Qayyum, Sumaira; Alsaedi, Ahmed; Ahmad, Bashir
Abstract: This paper explores the Darcy-Forchheimer two-dimensional flow of nanofluid due to curved stretching sheet. Brownian motion and thermophoresis effects are taken in to account. Bejan number and entropy generation are analyzed in presence of MHD, convective boundary conditions, partial slip and viscous dissipation. Nonlinear ordinary differential systems are developed through transformations. Convergent series solutions are constructed by using NDSolve of MATHEMATICA. Behavior of involved variables on flow characteristics is shown through graphs. Velocity reduces for higher slip parameter and Forchheimer number. Temperature and concentration have direct relation with thermal and solutal Biot numbers. An increase in entropy generation is seen for higher curvature parameter, porosity parameter and Brinkman number. Decrease in Bejan number is observed for higher estimations of Brinkman number and slip parameter. Comparative study of present results with previous information in a limiting sense is made.